Environmental regulations, GHRM and green innovation of manufacturing enterprises: evidence from China - Tu, Yulong; Lu, Lei; Wang, Shaojie (Frontiers in Environmental Science, 2024)
The contradiction between the economy and the environment is becoming more and more prominent. Green innovation is significant for Chinese manufacturing enterprises considering environmental and economic performance. Based on motivation theory and motivation crowding theory, this study aims to explore the impact of environmental regulations on green innovation of Chinese manufacturing enterprises and the mediating role of green human resource management between environmental regulations and green innovation of enterprises. The results of the empirical analysis of 127 manufacturing enterprises in Guangdong Province, China show that command-controlled regulation, market-incentivized regulation, and voluntary regulation positively impact enterprises' green innovation, and green human resource management positively affects enterprises' green innovation. Green human resource management only mediates the relationship between voluntary environmental regulation and green innovation. The study systematically reveals the driving mechanism of green innovation in Chinese manufacturing enterprises and enriches the relevant research on green innovation in manufacturing enterprises.